2012
DOI: 10.1371/journal.pone.0046399
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri Maintains a Functional Mucosal Barrier during DSS Treatment Despite Mucus Layer Dysfunction

Abstract: Treatment with the probiotic bacterium Lactobacillus reuteri has been shown to prevent dextran sodium sulfate (DSS)-induced colitis in rats. This is partly due to reduced P-selectin-dependent leukocyte- and platelet-endothelial cell interactions, however, the mechanism behind this protective effect is still unknown. In the present study a combination of culture dependent and molecular based T-RFLP profiling was used to investigate the influence of L. reuteri on the colonic mucosal barrier of DSS treated rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
97
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 28 publications
10
97
1
1
Order By: Relevance
“…Probiotic Lactobacillus-mediated interventions have been shown to downregulate TNF-a in the colon, enhance gut barrier activity, and reduce overall reductions in colitis-related pathology. [46][47][48][49] Additionally, treatment with probiotic Lactobacillus reuteri in mice abrogates the stressor-induced increases in the severity of the inflammatory response to a colonic pathogen. 40 Interestingly, though previous studies have found that Lactobacillus is reduced in the stool, 18,20,21,50 this study showed a reduction in mucosal epithelium-associated Lactobacillus but not in luminal lactobacilli, implying that psychological stressor exposure can have a distinct effects upon groups of mucosal microbiota compared to their luminal counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic Lactobacillus-mediated interventions have been shown to downregulate TNF-a in the colon, enhance gut barrier activity, and reduce overall reductions in colitis-related pathology. [46][47][48][49] Additionally, treatment with probiotic Lactobacillus reuteri in mice abrogates the stressor-induced increases in the severity of the inflammatory response to a colonic pathogen. 40 Interestingly, though previous studies have found that Lactobacillus is reduced in the stool, 18,20,21,50 this study showed a reduction in mucosal epithelium-associated Lactobacillus but not in luminal lactobacilli, implying that psychological stressor exposure can have a distinct effects upon groups of mucosal microbiota compared to their luminal counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33] It has also been shown that treatment with these probiotics can enhance mucus production and consequently improve the physical barrier protecting the epithelial layer. 34,35 Products of bacterial fermentation can also play an important role in maintaining the intestinal barrier. It has been shown that short-chain fatty acids can act as trophic factors for mucosal and epithelial layers.…”
Section: Effect Of Gut Microbiota On Intestinal Permeabilitymentioning
confidence: 99%
“…36,37 Impaired intestinal barrier function and consequent increased gut permeability can lead to increased translocation of gut bacteria across the intestinal wall and into the mesenteric lymphoid tissue. 34 Increased exposure of the ENS or mucosal immune cells to bacteria can provoke an immune response that can lead to release of inflammatory cytokines and activation of the vagus nerve and spinal afferent neurons. Inflammatory cytokines and the vagal system in turn can modulate the activity of the CNS and ENS.…”
Section: Effect Of Gut Microbiota On Intestinal Permeabilitymentioning
confidence: 99%
“…Although we observed the anti-inflammatory effects of the LAB pool in our rat model of acetic acid-induced colitis, when treating with Lactobacillus lactis, Steidler et al (2000) found no effect on dextran sodium sulfate-induced inflammation in mice or spontaneous colitis developed in IL-10-deficient mice. In contrast, Dicksved et al (2012), working with the same experimental model, found that Lactobacillus reuteri was able to maintain the barrier function of the mucosa, preventing microbial translocation, despite decreasing the mucus layer. The difference between these observations can probably be attributed to the use of different animal models and experimental settings.…”
Section: Discussionmentioning
confidence: 94%